The preventive effect of Chinese sumac fruit against monosodium urate-induced gouty arthritis in rats by regulating several inflammatory pathways. Issue 2 (5th January 2023) - Ma, Nan; Zhang, Yuanyue; Wang, Tao; Sun, Yilin; Cai, Shengbao
Abstract : Chinese sumac ( Rhus chinensis Mill.) fruit is a traditional Chinese medicinal material that can effectively prevent gouty arthritis in rats. Abstract : Chinese sumac ( Rhus chinensis Mill.) fruit is a traditional Chinese medicinal material that can be consumed daily. This study aimed to investigate whether the ethanol extract of sumac fruits can ameliorate monosodium urate-induced gouty arthritis in rats from the perspective of inflammation. Results showed that the extract of Chinese sumac fruits can obviously prevent monosodium urate-induced gouty arthritis in rats. Further analyses revealed that this bioactivity may be mainly achieved by modulating several inflammatory pathways, including NLRP3, NF-κB, and MAPK pathways. In addition, the extract can also improve oxidative stress by reducing the levels of malondialdehyde and myeloperoxidase, increasing the contents of superoxide dismutase and glutathione. In conclusion, this study revealed that the Chinese sumac fruit can alleviate the pathological symptoms of gouty arthritis by inhibiting inflammatory responses and oxidative stress, which can provide a theoretical basis for the use of Chinese sumac fruits as a Chinese herbal medicine and health food for the prevention and treatment of gouty arthritis.